Collaborative Referral Model to Achieve Hepatitis C Micro-Elimination in Methadone Maintenance Treatment Patients during the COVID-19 Pandemic - Chi-Ming Tai; Chun-Kai Huang; Te-Chang Changchien; Po-Chun Lin; Deng-Wu Wang; Ting-Ting Chang; Hsue-Wei Chan; Tzu-Haw Chen; Cheng-Hao Tseng; Chih-Cheng Chen; Chia-Ta Tsai; Yu-Ting Sie; et al. (Viruses, 2022)
Although hepatitis C virus (HCV) prevails in patients receiving methadone maintenance treatment (MMT), most do not receive anti-HCV therapy. This single-center observational study aimed to achieve HCV micro-elimination at an MMT center during the COVID-19 pandemic using a collaborative referral model, which comprised a referral-for-diagnosis stage (January 2020 to August 2020) and an on-site-diagnosis stage (September 2020 to January 2021). A multidisciplinary team was established and all MMT center patients were enrolled. HCV micro-elimination was defined as >90% of HCV-infected patients diagnosed and >80% of HCV-viremic patients treated. A total of 305 MMT patients, including 275 (90.2%) anti-HCV seropositive patients, were enrolled. Among 189 HCV-infected patients needing referral, the accumulative percentage receiving HCV RNA testing increased from 93 (49.2%) at referral-for-diagnosis stage to 168 (88.9%) at on-site-diagnosis stage. Among 138 HCV-viremic patients, the accumulative percentage receiving direct-acting antiviral (DAA) therapy increased from 77 (55.8%) at referral-for-diagnosis stage to 129 (93.5%) at on-site-diagnosis stage. We achieved an HCV RNA testing rate of 92.4% (254/275), an HCV treatment rate of 95.8% (203/212) and a sustained virological response rate of 94.1% (191/203). The collaborative referral model is highly effective in HCV RNA testing and HCV treatment uptake among MMT patients, achieving HCV micro-elimination.